Practice of tahajjud prayer among undergraduate medical students of IIUM and its relationship with poor sleep quality - Said, Abdul Hadi (2021)
Introduction: Tahajjud prayer is one of the highly rated spiritual practises among Muslims. It is a prayer performs in the last third of the night after Isha’ prayer, which requires a person to wake up from his sleep. This practice may interfere with their sleep and leads to poor sleep quality. This study aimed to assess the association between Tahajjud practice and poor sleep quality among medical students at the International Islamic University Malaysia (IIUM). Method: A cross-sectional study was conducted among 500 medical students in IIUM Kuantan using purposive and quota sampling. A validated self-reported questionnaire including Tahajjud practice and Pittsburgh Sleep Quality Index (PSQI) were distributed from 17th May to 19th July 2019. Descriptive statistics were used to measure the practice of Tahajjud and the prevalence of poor sleep quality. Logistic regression was used to measure the relationship between poor sleep quality and Tahajjud as well as other factors. Results: The response rate was 91.2%. The median number of Tahajjud performed was 1 night per week. The prevalence of poor sleep quality was 59.6%. Very interestingly, simple logistic regression analysis revealed that those performing Tahajjud were 13% less likely to have poor sleep quality compared to those who did not perform it. However, multiple logistic regression failed to find any significant relationship between Tahajjud and poor sleep quality. Conclusion: It is crucial to highlight that Tahajjud prayer did not lead to poor sleep quality among medical students. Since it is a highly rated practice in Islam, they should be encouraged to perform it.